2010
DOI: 10.1371/journal.pone.0012359
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo Biloba Extract Ameliorates Oxidative Phosphorylation Performance and Rescues Aβ-Induced Failure

Abstract: BackgroundEnergy deficiency and mitochondrial failure have been recognized as a prominent, early event in Alzheimer's disease (AD). Recently, we demonstrated that chronic exposure to amyloid-beta (Aβ) in human neuroblastoma cells over-expressing human wild-type amyloid precursor protein (APP) resulted in (i) activity changes of complexes III and IV of the oxidative phosphorylation system (OXPHOS) and in (ii) a drop of ATP levels which may finally instigate loss of synapses and neuronal cell death in AD. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 60 publications
6
70
1
1
Order By: Relevance
“…Therefore, we addressed this question in the present study by elevating APP and Aβ levels or Aβ levels alone in two distinct cell lines by the overexpression of APP or BACE1, respectively. Similar to other studies [25, 27, 28, 39] we observed a reduced mitochondrial respiration in cell lines overexpressing APP although the magnitude of reduction in our cells was lower. This could be due to the moderate increase in APP expression levels or due to the fact that we performed respirometry of intact instead of permeabilized cells.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we addressed this question in the present study by elevating APP and Aβ levels or Aβ levels alone in two distinct cell lines by the overexpression of APP or BACE1, respectively. Similar to other studies [25, 27, 28, 39] we observed a reduced mitochondrial respiration in cell lines overexpressing APP although the magnitude of reduction in our cells was lower. This could be due to the moderate increase in APP expression levels or due to the fact that we performed respirometry of intact instead of permeabilized cells.…”
Section: Discussionsupporting
confidence: 92%
“…Interesting data on the action/effects of EGB on different mitochondrial respiratory parameters and respiratory chain complexes were obtained by Rhein et al (2010) but due to different subjects investigated (human neuroblastoma cells in work of Rhein et al), different EGb preparations (EGb LI 1370), time of treatment and different compositions of media used for respiration measurements data comparison and analysis of reasons of differences of effects obtained in the work mentioned above and in our study is hardly possible. Fig.…”
Section: Discussionmentioning
confidence: 64%
“…Ginkgo biloba improves metabolic energy pathways through enhancement of the mitochondrial coupling state. Furthermore, the model showed substantial results for Ginkgo biloba as a long term therapeutic drug for AD (75).…”
Section: Therapeutic Drug Discoverymentioning
confidence: 96%